Single-lineage transcriptome analysis reveals key regulatory pathways in primitive erythroid progenitors in the mouse embryo - Isern, Joan (American Society of Hematology, 2011)
Primitive erythroid (EryP) progenitors are the first cell type specified from the mesoderm late in gastrulation. We used a transgenic reporter to image and purify the earliest blood progenitors and their descendants from developing mouse embryos. EryP progenitors exhibited remarkable proliferative capacity in the yolk sac immediately before the onset of circulation, when these cells comprise nearly half of all cells of the embryo. Global expression profiles generated at 24-hour intervals from embryonic day 7.5 through 2.5 revealed 2 abrupt changes in transcript diversity that coincided with the entry of EryPs into the circulation and with their late maturation and enucleation, respectively. These changes were paralleled by the expression of critical regulatory factors. Experiments designed to test predictions from these data demonstrated that the Wnt-signaling pathway is active in EryP progenitors, which display an aerobic glycolytic profile and the numbers of which are regulated by transforming growth factor-β1 and hypoxia. This is the first transcriptome assembled for a single hematopoietic lineage of the embryo over the course of its differentiation.